Cutaneous protothecosis on the bilateral wrists of a food handler. (1st January 2017) - Tan, M.; Pan, J. Y.; Chia, H. Y.; Oon, H. H.
Summary: Cutaneous protothecosis is caused by the achlorophyllic algae Prototheca, typically presenting as a localized plaque in immunocompetent individuals. We report a patient with bilateral erythematous plaques and pustules on her forearms, which had initially been treated with steroids for presumed eczema. Histology showed spherical spore‐like bodies with internal morula‐like septation, which were positive for periodic‐acid–Schiff (PAS) staining, consistent with cutaneous protothecosis. Definitive treatment with oral itraconazole resulted in resolution of the lesions.